Pengaruh Manajemen Laba, Capital Intensity Dan Karakter Eksekutif Terhadap Tax Avoidance Pada Perusahaan Sektor Property Dan Real Estate - Azzahra, Khoirunnisa; Prastiani, Siti Chaerunisa (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This research aims to determine and test the influence of earnings management, capital intensity, and executive character on tax avoidance. Empirical studies on property and real estate sector companies listed on the IDX for the 2017-2021 period. The hypothesis test used in this research is multiple linear regression analysis with the help of Eviews. The sample selection in this research used the purpose sampling method. The number of research samples based on predetermined criteria was 13 companies. The results of this research show that earnings management has a negative and significant effect on tax avoidance. capital intensity has no effect on tax avoidance. Executive character has a negative and significant effect on tax avoidance. Profit management, capital intensity, and executive character simultaneously influence tax avoidance. Sales growth is unable to moderate the influence of earnings management on tax avoidance